Pentingnya Peran Kepuasan Kerja sebagai Jembatan antara Kualitas Hubungan Pemimpin-Anggota dengan Komitmen Organisasional - Ayu Widiantari, Ni Putu Natih; Utomo, Kabul Wahyu; Wibowo, Martino (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to examine the impact of the quality of leader-member exchange towards organizational commitment with job satisfaction as an intervening variable on employees of The Central Statistics Office (BPS) in Bali. This study collects primary data via a self-enumerated questionnaire with 7-points Likert scale ranging from "Strongly Disagree" to "Strongly Agree." With a population of 264 employees, the sample method employed is saturated sampling or census. This study's sample had 173 respondents, with a response rate of 65.5% of the population. The SEM-PLS method was used to analyze the data with the Smart PLS 3.0 tool. The findings revealed that job satisfaction fully mediates the influence of the quality of the leader-member exchange on organizational commitment. The findings indicate that the quality of leader-member exchange may not necessarily boost employee’s organizational commitment if they are not satisfied with their jobs. As a result, in order to boost employee commitment, leader must be able to build quality relationships to increase the job satisfaction of his/her subordinates.